2017
DOI: 10.4085/1062-6050-52.8.01
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Stress Fractures in Collegiate Student-Athletes, 2004–2005 Through 2013–2014 Academic Years

Abstract: Women experienced stress fractures at higher rates than men, more often in the preseason, and predominantly in the foot and lower leg. Researchers should continue to investigate biological and biomechanical risk factors for these injuries as well as prevention interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
123
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(138 citation statements)
references
References 38 publications
(53 reference statements)
6
123
0
7
Order By: Relevance
“…Due to the nature of the study, that uses a self-reported questionnaire for data collection, the exact anatomical location of the overuse injuries cannot be indicated. However, our finding that about 60% of the SF was localized at the lower limbs is consistent with data from other authors, who pointed out me ta tarsals and tibia as most commonly affected by stress fractures bones (Chen et al, 2013;Rizzone et al, 2017;Sharma & Heagerty, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Due to the nature of the study, that uses a self-reported questionnaire for data collection, the exact anatomical location of the overuse injuries cannot be indicated. However, our finding that about 60% of the SF was localized at the lower limbs is consistent with data from other authors, who pointed out me ta tarsals and tibia as most commonly affected by stress fractures bones (Chen et al, 2013;Rizzone et al, 2017;Sharma & Heagerty, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Incidence rate among swimmers is typically difficult to estimate due to various factors, such as the unusual occurrence of this type of injury, and the reported single case studies in the literature. From the literature, one study has provided very low incidence rate (ranging from 0.58 to 1.66) in collegiate student athletes who participate in swimming and diving (Rizzone et al, 2017). However, it is difficult to compare the incidence of stress fractures in different sports because of a lack of sound epidemiologic data.…”
Section: Discussionmentioning
confidence: 99%
“…One point that we also make is that larger, prospective longitudinal or retrospective studies can provide more value although more technically difficult and time consuming. We always hope that one day we can do meta-analysis of data similar to a study by Rizzone et al [6] where they analysed 11,778,145 athlete exposures and evaluated the incidence and recurrence of stress fractures in student athletes, which were reported in only 671 cases. This huge study spanned for 9 years and was able to evaluate the incidence of recurrence of stress fractures and is the ideal to be strived for in veterinary medicine.…”
Section: Dear Editormentioning
confidence: 99%